DEVELOPMENT TENDENCIES AND CLASSIFICATION OF PROGRAMMING LANGUAGES TEACHED IN HIGH SCHOOLS - Jumanqo‘ziyev O‘ktamjon O‘tkirjon o‘g‘li; Fayziyeva Maxbuba Raximjonovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article analyzes the development trends of programming languages in general secondary schools and their principles of operation.